The Influence of Work-Life Balance on Employee Performance at Yuofu Fa Steel Co., Ltd. - Mohamad Al Bas; Candra Pramula Pinandita (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2026)
The issue of work-life balance is increasingly becoming a focal point in human resource management studies. This phenomenon arises along with the increasing demands of the working world for productivity, efficiency, and full engagement from employees, especially in heavy industry sectors such as steel manufacturing. It provides a theoretical contribution to the development of studies on work-life balance, particularly in the context of heavy manufacturing industries, which are still rarely the main focus. Practically, the results of this research serve as a source or benchmark for company management in formulating work policies that are more balanced and responsive to employee needs. This research employs a descriptive qualitative approach aimed at elaborating and deeply understanding the influence of work-life balance on employee performance at YUOFU FA STEEL CO., LTD. The research results indicate that work-life balance significantly influences employee performance at YUOFU FA STEEL CO., LTD. The imbalance between work demands and personal life has become the main issue felt by the majority of employees. This imbalance is primarily due to long working hours, an almost mandatory overtime system every day, and a lack of flexibility in work schedule arrangements. According to the results of in-depth interviews and direct observations, the majority of employees stated that they did not have enough time to rest, gather with family, or engage in other social activities. This condition significantly impacts physical and mental health, which ultimately reduces work quality, focus, and employee morale